Research on nonlinear dynamic vertical vibration characteristics and control of roll system in cold rolling mill - Li Li; Chenhao Zhong (Scientific Reports)
Abstract In order to address the vertical vibration phenomenon of the working roll during the rolling process, taking into consideration the nonlinear factors of the rolling interface and the roll system, this study establishes a nonlinear excitation vertical vibration model based on dynamic rolling force. The impact of nonlinear factors on system stability and vibration characteristics is analyzed. The study reveals that nonlinear damping and linear stiffness exhibit significant effects through time delay characteristics. Nonlinear stiffness has a drastic impact on system stability, while increasing system damping effectively reduces the amplitude and narrows the resonance region. By employing averaging method and singular value theory, the stability of the cold rolling mill roll system is analyzed under non-autonomous and autonomous states. A combined time-delay feedback controller is proposed, which effectively suppresses the system’s large-scale vibration by adjusting the control gain and time delay parameters. MATLAB simulations are conducted to validate the accuracy of the control strategy, providing theoretical support for vibration prediction and system design in rolling mills.